Komunikasi Organisasi Dalam Menangani Konflik Hubungan Pekerjaan di PT. Elephant Agung Perkasa - Afnan Alifiyan; Mochammad Mirza; Riza Gusti Rahayu (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to investigate and find solutions to the existing problems at PT. Elephant Agung Perkasa, focusing on Organizational Communication perspectives to address and resolve issues as well as inhibiting factors within the company. The study adopts a qualitative approach with a constructivist framework. Data collection involves observation and in-depth interviews to gather information for addressing the researched problems. The results indicate that the communication role at PT. Elephant Agung Perkasa is closely tied to the system implemented from superiors to employees and the communication among colleagues. To effectively manage organizational communication, PT. Elephant Agung Perkasa needs to handle it efficiently in both maintaining and resolving conflicts, as identified in this research. This ensures the company can implement effective communication practices and receive positive feedback from employees.